Research of special limits during heat treatment of materials in the two-phase region under supercritical temperature influence - Sereda, B.; Kryhliyak, I.; Sereda, D.; Voloh, V. (Problems of Atomic Science and Technology, 2023)
The results of the research on establishing the dependence of the coercive force (Нs) on special boundaries in a low-carbon alloy are given. Annealing at a temperature of 900 °С with a holding time of 1 to 3 h leads to an increase in the number of special boundaries from 22.7 to 37.17% and to an increase in magnetic permeability and, accordingly, a decrease in the coercive force from 1.60 to 1.24 A/cm. When the load is axially stretched, the coercive force changes. The initial stage of plastic deformation is most sensitive to the growth of coercive force, which allows us to identify areas in which local plastic deformation has occurred, which indicates a significant decrease in the operational characteristics of parts. Наведено результати дослідження по встановленню залежності величини коерцитивної сили (Нс) на спеціальні границі в низьковуглецевому сплаві. Відпал при температурі 900 °С з витримкою від 1 до 3 год призводить до збільшення кількості спеціальних границь з 22,7 до 37,17% та до збільшення магнітної проникності й відповідно зниження величини коерцитивної сили з 1,60 до 1,24 А/см. При осьовому розтягуванні навантаження змінюється коерцитивна сила. Початкова стадія пластичної деформації найбільш чутлива до зростання коерцитивної сили, що дозволяє виявити ділянки, в яких сталася локальна пластична деформація, що свідчить про значне зниження експлуатаційних характеристик деталей.